A review on South Asian wheat blast: The present status and future perspective. (13th August 2020) - Yesmin, Nabila; Jenny, Farhana; Abdullah, Hasan M.; Hossain, Motaher M.; Kader, Md A.; Solomon, Peter S.; Bhuiyan, Md A. H. B.
Abstract: The outbreak of wheat blast ( Pyricularia oryzae, syn. Magnaporthe oryzae ) in Bangladesh and India in recent times is a cause of grave concern for future wheat production in South Asian countries. In this review, we focus on the origin and pathology of P . oryzae and its current status and impact on trade of wheat in South Asia. We also consider future directions for efficient detection, monitoring, forecasting, and managing this destructive disease. Proper detection and monitoring are essential for imposing disease management strategies. Cutting‐edge tools such as geospatial modelling and remote sensing technologies based on field observation will be pivotal to efficiently contain and manage the disease. Strong quarantine regulations too are critical in preventing the pathogen movement and are also discussed within. Complementary approaches, such as the induction of systemic resistance by applying plant growth‐promoting rhizobacteria or probiotic bacteria, are also considered here. This review provides a comprehensive summary on the status of wheat blast in South‐East Asia and will provide an important resource for wheat blast research in the affected areas. Abstract : This review provides a comprehensive summary on the status of wheat blast in South‐East Asia and provides an important resource for wheat blast research in the affected areas.